PERANCANGAN BALANCED SCORECARD SEBAGAI ALAT UNTUK ANALISIS KINERJA PADA IBI DARMAJAYA - lestari, winda rika (Jurnal Manajemen dan Keuangan, 2010)
IBI Darmajaya is one university in Lampung, which is always increased student growth from year to year. In its growth the IBI Darmajaya not have a comprehensive performance measurement method, to determine the position of IBI Darmajaya and improve their performance in the education industry in Lampung. The purpose and benefits in this study weeks to obtain the design model of the Balanced Scorecard performance measurement is accurate and appropriate for the IBI Darmajaya and measure its performance with the design model. The method used is a survey method and the method of literature. The method uses a questionnaire survey using a total sample of respondents and a sample of 94 student employees and faculty as much as 113 respondents (stratified random sampling method). The results showed that the design of the Balanced Scorecard on the financial perspective with the Current Ratio, Net Profit Margin, Return on Investment and Working Capital Turnover, all indicate the level of capability in operational funding and good liquidity. Customer perspective on student growth increased, the students who do not register due to work elsewhere 46.86% and 35.29% economic limitations. Internal business process perspective, the ratio of faculty to students in the effectiveness of class 1: 24. Lecturer S1 55%, 44% S2, and S3 1.6%, the level of lecturer performance both visible from the monitoring results on average in 2007 of 6.9. But universities should improve the quality of its library. And in the perspective of growth and learning, still less so in workshops, training and further studies are given to employees and lecturers. From Tridarma college and community service element of research still must be improved.Keyword: Balanced Scorecard, Performance.